Real-time three-dimensional passive cavitation detection for clinical high intensity focussed ultrasound systems - Collin, J; Coviello, C; Lyka, E; Leslie, T; Coussios, C (2013)
Bubble activity during High Intensity Focussed Ultrasound (HIFU) surgery has been linked with desirable effects, such as an enhanced heat deposition caused by inertial cavitation, and undesirable effects, such as lesion migration caused by boiling bubbles. There is presently no reliable way of achieving spatiotemporal monitoring of cavitation activity during clinical HIFU treatments. In the present work, a near-acoustically-transparent two-dimensional 32-element PVDF array was designed and mounted on the therapy transducer of a clinical HIFU device (Model JC200, Chongqing Haifu) to enable detection of acoustic emissions arising from cavitation during therapy. The signal detected by each of the elements was digitized and processed in real time on a Graphical Processing Unit (GPU), and beamformed using our previously described Passive Acoustic Mapping (PAM) algorithm to produce real-time three-dimensional (3D) maps of cavitation activity with a frame rate in excess of 5 Hz. The system was initially validated in agar-based tissue-mimicking materials, demonstrating that the displayed volume of cavitation activity agreed with predictions based on in situ pressure calibrations. The system was further validated during clinical HIFU treatments of kidney tumour, liver tumour and uterine fibroid ablation, and was found to enable accurate localization of the HIFU focus at sub-lesioning intensities. © 2013 Acoustical Society of America.